Participatory Exhibitions as An Awareness-raising Platform for Bird Window Collisions - Castro, Janina Carla; Gan, Jelaine; Longnecker, Nancy (UI Scholars Hub, 2025)
Bird window strikes pose a significant threat to avian populations in urban settings. Understanding public attitudes toward this issue is vital for communicating the problem and possible interventions, such as applying window stickers. Bird Window Strike Philippines, a citizen science initiative, has promoted awareness through online engagement and a public pop-up exhibition designed to leave a lasting impression and gather visitor feedback. The exhibition introduced Filipino audiences to bird-window collisions through educational and participatory elements, including interpretive panels, taxidermied bird specimens, and window models demonstrating prevention techniques. Its central message was: “Bird window strikes are a problem, and we can be part of the solution.” The taxidermied birds were included to foster emotional connection. Visitors participated by voting on preferred preventive measures and answering questions about what would encourage them to adopt these interventions. Comment cards captured their reflections and takeaways. Results showed a clear preference for window stickers and mesh and a desire for affordable and accessible options. Notably, emotional engagement was evident among participants, reflecting the exhibition’s capacity to foster empathy and deeper reflection. Open-ended responses highlighted key themes: human agency in mitigating collisions, the conservation significance of window strikes, the role of citizen science and public awareness, and the underestimated frequency of such events. The exhibition served to raise awareness of this often-overlooked conservation issue. The study supports public exhibitions as effective tools for fostering dialogue and building biodiversity-inclusive urban environments.